2012
DOI: 10.1590/s0103-50532012005000030
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of novel quinolines using TsOH/ionic liquid under microwave

Abstract: Neste trabalho, 3-haloacetil-4-metilquinolinas foram sintetizadas a partir da reação de 4-alcóxi-3-alquen-2-onas [R In this work, 3-haloacetyl-4-methylquinolines were synthesized from the reaction of 4-alkoxy-3-alken-2-ones [R 1 C(O)CH=C(R 2 )OCH 3 , where R 1 = CF 3 , CCl 3 , CHCl 2 , CF 2 Cl, CF 2 CF 3 and R 2 = Me, Et, Pr, Bu, i-Bu and i-Pe] and 2-aminoacetophenone. The reaction was performed in ionic liquid and 4-toluene sulfonic acid under microwave irradiation. Results showed that the catalytic method wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…[26] However, the synthesis of trifluoroacetylquinolines was rarely reported. [27,28] In 2020 and 2021, a novel and efficient method for synthesis of trifluoromethylpyridines 5 and 7, trifluoromethyl-quinolines 10, or trifluoroacetyl-quinoline derivatives 12 from the reactions of trifluoromethyl-α,β-ynones 3 with β-enamino esters (or ketones) 4, vinyl azides 6, acetanilides 8, anilides, 9 or quinolines 11 in the presence of ZnBr 2 , CuBr 2 /PPh 3 / PMDETA, [RhCp*Cl 2 ] 2 /AgSbF 6 , or morpholine was described by the groups of Hu, Trofimov, Nenajdenko, Wu, Wang, and Cheng (Scheme 3). [10,[29][30][31] The results indicated that the reactions between trifluoromethyl-α,β-ynones 3 and β-enamino esters (or ketones) 4 catalyzed by ZnBr 2 gave 40-82% yields of trifluoromethyl-pyridines 5 except when R 2 in substrates 4 was CF 3 .…”
Section: Synthesis Of Trifluoromethylpyridines Trifluoromethyl-quinol...mentioning
confidence: 99%
“…[26] However, the synthesis of trifluoroacetylquinolines was rarely reported. [27,28] In 2020 and 2021, a novel and efficient method for synthesis of trifluoromethylpyridines 5 and 7, trifluoromethyl-quinolines 10, or trifluoroacetyl-quinoline derivatives 12 from the reactions of trifluoromethyl-α,β-ynones 3 with β-enamino esters (or ketones) 4, vinyl azides 6, acetanilides 8, anilides, 9 or quinolines 11 in the presence of ZnBr 2 , CuBr 2 /PPh 3 / PMDETA, [RhCp*Cl 2 ] 2 /AgSbF 6 , or morpholine was described by the groups of Hu, Trofimov, Nenajdenko, Wu, Wang, and Cheng (Scheme 3). [10,[29][30][31] The results indicated that the reactions between trifluoromethyl-α,β-ynones 3 and β-enamino esters (or ketones) 4 catalyzed by ZnBr 2 gave 40-82% yields of trifluoromethyl-pyridines 5 except when R 2 in substrates 4 was CF 3 .…”
Section: Synthesis Of Trifluoromethylpyridines Trifluoromethyl-quinol...mentioning
confidence: 99%
“…Prola et al . described the synthesis of novel 3‐haloacylquinolines from 4‐alkoxyvinyl ketones and 2‐aminoacetophenone using TsOH/IL under MW irradiation. It was demonstrated that the synergic effects of ILs and MW operate during the synthesis of quinolines, resulting in short reaction time and good yields.…”
Section: Synthesis Of Heterocyclic Compoundsmentioning
confidence: 99%
“…Martins et al [202] Wang et al [206] also reported a three-component reaction of aryl aldehydes, cyclic β-enaminones, and different active methylene compounds for synthesis of quinolines 116 (Scheme 63) in the presence of [BMIM][BF 4 ] in a molar ratio of 1:52 (reactant/IL). For the series of aldehydes used in these reactions, they found that there was no apparent effect produced from the electronic nature of the aromatic ring substituents.…”
Section: Quinolinesmentioning
confidence: 99%
“…The IL was recycled and reused without any loss of activity[202].Srinivasan et al[203] investigated the synthesis of quinolines 112 using the Friedlander heteroannulation tactic by reaction of aminoacetophenones 111 with a variety of ketones or ketoesters in the presence of BBIM and HBIM salts (Scheme 61). (Scheme 60).…”
mentioning
confidence: 99%